2018
DOI: 10.3390/su10030668
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Eco-Efficiency of Agro-Products’ Closed-Loop Supply Chain under the Belt and Road Initiatives: A System Dynamics Approach

Abstract: This study redesigns the supply chain of agricultural products in southwest China under the Belt and Road Initiative to improve its eco-efficiency by considering the associated agro-wastes flowing into bioenergy enterprise for energy production. Two scenarios are created, in which the first assumes that all waste flows into the enterprise, whereas the second only considers the inflow of agro-waste produced by farmers and the wholesale market. A system dynamics simulation is conducted by using carbon emissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Prior studies have focused on the optimization of sequential MSW disposal systems, indicated from waste generation to the final disposal [39,40]. This study deliberately narrows down the systems boundary by only taking the disposal design into account, since countries under the Belt and Road Initiative have not formulated the appropriate plan to reduce the stocks of waste [41]. Moreover, the facilities for waste disposal are generally operated independently, without developing possible linkages among them [11,42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies have focused on the optimization of sequential MSW disposal systems, indicated from waste generation to the final disposal [39,40]. This study deliberately narrows down the systems boundary by only taking the disposal design into account, since countries under the Belt and Road Initiative have not formulated the appropriate plan to reduce the stocks of waste [41]. Moreover, the facilities for waste disposal are generally operated independently, without developing possible linkages among them [11,42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the aspect of low carbon emissions and climate change, Liu, Zhao [5] used the waste material agro-straw to develop an integrated model of multi-objective optimization and system dynamics to simulate the optimal straw-to-electricity structure and explore the path toward enhancing the sustainability of this structure. Zhao, Liu [6] conducted a similar research and determined the lowest carbon emission 2 of 18 scenario to drive the closed-loop supply chain operations of agro-products. Regarding environmental pollution, Li, Wu [7] studied the distribution, enrichment, and sources of trace metals in the topsoil near a steel wire plant along the Silk Road Economic Belt in northwest China.…”
Section: Introductionmentioning
confidence: 99%
“…The research on the "Internet+" fresh agricultural product supply chain has developed from the initial research on the theoretical framework of fresh agricultural products ecommerce to the development of fresh agricultural products supply chain and operation. Design global supply chain system of food via electronic marketing [1], analyses data for Supply Chain Management [2], elate Information systems more flexible, proposed a Semantic Metadata Enrichment Software Ecosystem [3], Using IOT in Analysis and Monitoring Agricultural Field [4], using long short term memory analysis of RFID supply chain path [5], under the Belt and Road Initiatives, use a system dynamics approach enhancing ecological benefits of agro-products' Closed-Loop supply chain [6], handling uncertainty in agricultural supply chain management [7], zero-packaging grocery stores to improve the social and environmental impacts of the food supply chain [8]. Use e-commerce service platform for agreement based circulation of fruits and vegetables on supply chain management [9], research on cold chain logistics of fresh produce in China [10].…”
Section: Introductionmentioning
confidence: 99%